Near-infrared spectroscopy assessment of cerebral oxygen metabolism in the developing premature brain - Roche-Labarbe, Nadège (Nature Publishing Group, 2012)
Little is known about cerebral blood flow, cerebral blood volume (CBV), oxygenation, and oxygen consumption in the premature newborn brain. We combined quantitative frequency-domain near-infrared spectroscopy measures of cerebral hemoglobin oxygenation (SO(2)) and CBV with diffusion correlation spectroscopy measures of cerebral blood flow index (BF(ix)) to determine the relationship between these measures, gestational age at birth (GA), and chronological age. We followed 56 neonates of various GA once a week during their hospital stay. We provide absolute values of SO(2) and CBV, relative values of BF(ix), and relative cerebral metabolic rate of oxygen (rCMRO(2)) as a function of postmenstrual age (PMA) and chronological age for four GA groups. SO(2) correlates with chronological age (r=−0.54, P value ⩽0.001) but not with PMA (r=−0.07), whereas BF(ix) and rCMRO(2) correlate better with PMA (r=0.37 and 0.43, respectively, P value ⩽0.001). Relative CMRO2 during the first month of life is lower when GA is lower. Blood flow index and rCMRO(2) are more accurate biomarkers of the brain development than SO(2) in the premature newborns.